Religiosity and Piety Motivation in Islamic Medical Tourism Choices in Indonesia - Firdaus Firdaus; Jumai Jumai; Zailani bin Abdulah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
This study examines the relationships among Religiosity, Islamic Hospital Image, Motivation of Piety, and Behavioral Intention in Choosing Islamic Medical Tourism Destinations (IMTD) in Indonesia. The research aims to analyze both the direct and indirect effects of religiosity and Islamic hospital image on behavioral intention through the mediating role of motivation of piety within the context of Islamic medical tourism. A quantitative explanatory research design was employed using a cross-sectional survey approach. Data were collected from 220 Indonesian Muslim respondents who were familiar with Islamic healthcare services and medical tourism concepts. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that Islamic Hospital Image has a positive and significant effect on Behavioral Intention (β = 1.308; p = 0.000), while Religiosity has a positive and significant effect on Motivation of Piety (β = 1.422; p = 0.000). The study contributes to the extension of the Theory of Planned Behavior (TPB) by integrating religiosity, Islamic hospital image, and motivation of piety into the context of Islamic medical tourism . The findings suggest that institutional healthcare perceptions play a more direct role in shaping behavioral intention, while religiosity operates indirectly through internal motivational mechanisms.